High throughput fabrication of mesoporous carbon perovskite solar cells. Issue 35 (21st August 2017) - Baker, Jenny; Hooper, Katherine; Meroni, Simone; Pockett, Adam; McGettrick, James; Wei, Zhengfei; Escalante, Renán; Oskam, Gerko; Carnie, Matthew; Watson, Trystan
Abstract : Near infrared sintering in less than 25 seconds for enhanced commercial viability of screen printed perovskite solar cells. Abstract : The screen printed mesoporous carbon perovskite solar cell has great potential for commercialisation due to its scalable deposition processes and use of inexpensive materials. However, each layer requires long high temperature heating steps to achieve the necessary sintering and porosity, which is very time and energy intensive for large scale production. Near infrared processing is demonstrated here to reduce the heating time of mesoporous layers within a fully printed lead halide perovskite solar cell from 2 hours to 30 seconds. A stabilised efficiency of 11% was achieved by processing in 30 seconds, identical to that of devices heated in 2 hours. For the first time the effect of residual binder in the carbon electrode on the electron lifetime and charge transfer within devices has been investigated. Furthermore cross section EDX mapping of perovskite infiltration provides a greater understanding into the processing requirements of these devices vital to enable commercialisation.